2017
DOI: 10.1161/jaha.117.006683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Febuxostat on Ambulatory Blood Pressure in Subjects With Hyperuricemia and Hypertension: A Phase 2 Randomized Placebo‐Controlled Study

Abstract: BackgroundHyperuricemia is associated with hypertension, with elevated serum uric acid levels postulated to have a causal role in the development of hypertension. Consequently, serum uric acid reduction may help lower blood pressure (BP). A Phase 2, double‐blind, placebo‐controlled trial was conducted to assess the potential BP‐lowering effects of the xanthine oxidase inhibitor febuxostat in subjects with hypertension and hyperuricemia (serum uric acid ≥0.42 mmol/L [≥7.0 mg/dL]).Methods and ResultsSubjects (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 31 publications
(60 reference statements)
0
38
0
2
Order By: Relevance
“…189,190 The third multicenter trial included 109 adults (aged ≥ 18 years) with primary hypertension. 193 The use of febuxostat, compared with placebo, was evaluated over 6 weeks. No significant difference between the febuxostat and placebo groups was found in ambulatory daytime or nighttime BP, or clinic SBP or DBP, from baseline to week 6.…”
Section: Therapeutic Management Of Hyperuricemia and Effects On Bp Comentioning
confidence: 99%
“…189,190 The third multicenter trial included 109 adults (aged ≥ 18 years) with primary hypertension. 193 The use of febuxostat, compared with placebo, was evaluated over 6 weeks. No significant difference between the febuxostat and placebo groups was found in ambulatory daytime or nighttime BP, or clinic SBP or DBP, from baseline to week 6.…”
Section: Therapeutic Management Of Hyperuricemia and Effects On Bp Comentioning
confidence: 99%
“…SGLT2 inhibitors increase the concentration of glucose in the proximal tubules, and current evidence indicates that the glucose competes with urate for the facilitative hexose/urate transporter GLUT9b, reducing urate reabsorption. Abbreviations: ABCG2, ATP-binding cassette transporter G2; GLUT9a/b, glucose transporter SLC2A9 isoform a or b; MRP-4, multidrug resistance-associated protein-4; NPT, sodium/phosphate co-transporter; OAT, organic anion transporter; SGLT, sodium/glucose co-transporter; URAT1, urate transporter SLC22A12 allopurinol and febuxostat which reduce uric acid production, modestly reduce blood pressure in hypertensive patients independently of antihypertensive therapies [50][51][52][53][54]. This suggests a possible pathogenic role of elevated uric acid in the development of elevated blood pressure.…”
mentioning
confidence: 99%
“…Based on the important role of XOR in the regulation of the nitrate–nitrite–NO pathway, one may speculate that chronic inhibition of this enzyme could be associated with adverse cardiovascular and renal effects, which is in contrast with that hypothesized in several studies . A recent study demonstrated that 8‐week treatment with febuxostat did not significantly alter renal and intraglomerular haemodynamics or systemic vascular functional parameters in healthy subjects .…”
Section: Mechanisms Contributing To Antioxidative Effects Of the Nitrmentioning
confidence: 93%